2021
DOI: 10.3390/atmos12020137
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Simulation of Polar Lows over Norwegian and Barents Seas Using the COSMO-CLM and ICON Models for the 2019–2020 Cold Season

Abstract: The lack of meteorological observations at high latitudes and the small size and relatively short lifetime of polar lows (PLs) constitute a problem in the simulation and prediction of these phenomena by numerical models. On the other hand, PLs, which are rapidly developing, can lead to such extreme weather events as stormy waves, strong winds, the icing of ships, and snowfalls with low visibility, which can influence communication along the Arctic seas. This article is devoted to studying the possibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…The PL case study was documented by Revokatova et al. (2021) as well. PLs are small, but intense mesoscale cyclones forming in cold air masses over the ocean with a maximum extent of 600 km diameter (Rojo et al., 2015; Stoll et al., 2018).…”
Section: Results: Data Assimilation Diagnosticsmentioning
confidence: 88%
See 1 more Smart Citation
“…The PL case study was documented by Revokatova et al. (2021) as well. PLs are small, but intense mesoscale cyclones forming in cold air masses over the ocean with a maximum extent of 600 km diameter (Rojo et al., 2015; Stoll et al., 2018).…”
Section: Results: Data Assimilation Diagnosticsmentioning
confidence: 88%
“…The AA background valid at 26 November 2019 12 UTC, and the result of a 3 hr forecast initiated from the 09 UTC analysis has been investigated. The PL case study was documented by Revokatova et al (2021) as well. PLs are small, but intense mesoscale cyclones forming in cold air masses over the ocean with a maximum extent of 600 km diameter (Rojo et al, 2015;Stoll et al, 2018).…”
Section: Model Wind Variabilitymentioning
confidence: 99%
“…Indeed, many studies found large discrepancies between different observed gridded datasets despite that they are all based on weather stations (Prein & Gobiet, 2017; Zittis et al, 2017). This is especially true in low‐density populated polar (Revokatova et al, 2021) and mountainous regions where weather stations are sparsely distributed. In addition, weather stations are affected by precipitation undercatch (Gao, Chen, & Jiang, 2020; Neff, 1977; Pollock et al, 2018), which is even more severe for snow measurements in winter (Fortin et al, 2008; Gao, Chen, & Jiang, 2020; Hughes et al, 2020; Rasmussen et al, 2012).…”
Section: Methodology and Principles Behind Cprcmsmentioning
confidence: 99%
“…For more than a decade, CPRCMs have been used to simulate regional surface wind over complex terrain (Jiménez et al, 2010), offshore (Jiménez et al, 2015), and during storms (Schaaf & Feser, 2018; Platonov & Kislov, 2020) and polar lows (Revokatova et al, 2021). CPRCMs were deemed quite useful to identify regions with high wind energy potential (Carvalho et al, 2012) and where observational coverage could be improved (Jiménez et al, 2010).…”
Section: Cprcm Benefits For Impact Studiesmentioning
confidence: 99%
“…Spherical icosahedral grid is often used as the basic framework of atmospheric models, such as the ICosahedral Nonhydrostatic model (ICON) [1-3], Models for Predication Across Scales (MPAS) [4], the Non-hydrostatic ICosahedral Atmospheric Model (NICAM) [5], DYNAMICO [6], Ocean-Land-Atmosphere Model (OLAM) [7,8], etc. These models are wieldy used for polar lows simulation [9], monsoon simulation [10], ocean tides dissipation [11], etc. Recently, the Spectral Radiation Transport Model for Aerosol Species coupled with NICAM (NICAM-SPRINTARS) [12] has been developed for studying and simulating atmosphere-aerosols interactions and their effects on atmospheric pollution and climate change.…”
Section: Introductionmentioning
confidence: 99%